"They think we're OK and we know we're not". A qualitative study of asylum seekers' access, knowledge and views to health care in the UK - O'Donnell, Catherine A (BioMed Central, 2007)
BACKGROUND: The provision of healthcare for asylum seekers is a global issue. Providing appropriate and culturally sensitive services requires us to understand the barriers facing asylum seekers and the facilitators that help them access health care. Here, we report on two linked studies exploring these issues, along with the health care needs and beliefs of asylum seekers living in the UK. METHODS: Two qualitative methods were employed: focus groups facilitated by members of the asylum seeking community and interviews, either one-to-one or in a group, conducted through an interpreter. Analysis was facilitated using the Framework method. RESULTS: Most asylum seekers were registered with a GP, facilitated for some by an Asylum Support nurse. Many experienced difficulty getting timely appointments with their doctor, especially for self-limiting symptoms that they felt could become more serious, especially in children. Most were positive about the health care they received, although some commented on the lack of continuity. However, there was surprise and disappointment at the length of waiting times both for hospital appointments and when attending accident and emergency departments. Most had attended a dentist, but usually only when there was a clinical need. The provision of interpreters in primary care was generally good, although there was a tension between interpreters translating verbatim and acting as patient advocates. Access to interpreters in other settings, e.g. in-patient hospital stays, was problematic. Barriers included the cost of over-the-counter medication, e.g. children's paracetamol; knowledge of out-of-hours medical care; and access to specialists in secondary care. Most respondents came from countries with no system of primary medical care, which impacted on their expectations of the UK system. CONCLUSION: Most asylum seekers were positive about their experiences of health care. However, we have identified issues regarding their understanding of how the UK system works, in particular the role of general practitioners and referral to hospital specialists. The provision of an Asylum Support nurse was clearly a facilitator to accessing primary medical care. Initiatives to increase their awareness and understanding of the UK system would be beneficial. Interpreting services also need to be developed, in particular their role in secondary care and the development of the role of interpreter as patient advocate.